2018
DOI: 10.1038/s41598-018-32823-2
|View full text |Cite
|
Sign up to set email alerts
|

Exploring photosensitization as an efficient antifungal method

Abstract: Lipid bilayers containing ergosterol show signs of destruction when they are treated with singlet oxygen, due to the conversion of ergosterol into its peroxy derivative. Applying this previous knowledge, an antifungal method was explored using Candida tropicalis as model, and membrane permeation under photosensitization conditions became evident. These data were complemented through AFM images of artificial lipid bilayers, using cholesterol or ergosterol as structural sterols, showing their corresponding morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…Previous studies demonstrated that the higher content of ergosterol was related to the higher resistance of the strain [60,61]. Jiang et al found that the average ergosterol content in the resistant group was higher than that in the susceptible group [62].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies demonstrated that the higher content of ergosterol was related to the higher resistance of the strain [60,61]. Jiang et al found that the average ergosterol content in the resistant group was higher than that in the susceptible group [62].…”
Section: Discussionmentioning
confidence: 98%
“…AFM topographic images were obtained in Peak Force mode using a multimode microscope with a Nanoscope V control unit from Bruker. Scan rates of 0.5–1.2 Hz and FESP (50–100 kHz, and 1–5 N m-1) tips (from Bruker) were used 37 . To get representative information about the hemolysis process of the RBCs images from (100 µm × 100 µm) to (0.6 µm × 0.6 µm) were recorded using 512 points/line.…”
Section: Methodsmentioning
confidence: 99%
“…Immediately, the red fluorescence of PI, which indicates membrane damage, was observed using a fluorescence microscope with an excitation filter of 550 nm and an emission filter of 615 nm. Control experiments were performed to ensure that CH–PPIX and PPIX do not show observable fluorescence emission at the concentrations used. …”
Section: Methodsmentioning
confidence: 99%